Vulnerability, social value and the equitable sharing of benefits from research: beyond the placebo and access debates - Kurihara, Chieko; Greco, Dirceu; Dhai, Ames; Matsuyama, Kotone; Baroutsou, Varvara (Frontiers in Medicine, 2024)
The vulnerability of research participants is a critical topic for the 2024 revision of the Declaration of Helsinki, with the proposal to include "social value". However, this proposal has been withdrawn and the relationship between the two concepts has not been clarified. This paper attempts to clarify: 1.the recent reform for the ethical inclusion of vulnerable study participants to promote diversity; 2. the social value, prerequisite for everyone, especially for those who are vulnerable and the most in need; 3. the requirements for promoting the inclusion of vulnerable participants, in particular the review of the norms for placebo-controlled trials and post-trial access; 4. finally, the direction of research ethics reform to achieve social value and equitable global health.